PERTIMBANGAN HAKIM DALAM MEMUTUSKAN PERKARA DISPENSASI NIKAH BERDASARKAN ANALISIS MASLAHAH (Studi Penetapan Hakim No. 266/Pdt.P/2020/PA.Pwr di Pengadilan Agama Purworejo) - Waluyo Sudarmaji (Al-Syakhsiyyah: Journal of Law & Family Studies, 2021)
In the event that the prospective bride and groom will hold a marriage registered at the local Office of Religious Affairs If the age is less than 19 years, it will be rejected because the marriage conditions are not fulfilled. Because the marriage is considered urgent to be carried out, then parents or guardians can apply for a marriage dispensation at the Religious Court. Marriage dispensation is an application for ratification of a marriage that will take place by the prospective bride and groom or one of the prospective brides who are not old enough to marry. This research is the result of research on the consideration of judges in deciding the case of marital dispensation with the analysis of maslahah with the main problem of consideration of judges in deciding the case and the analysis of maslahah. This research is analitive descriptive qualitative research with normative approach, data source used by primary data source in the form of interviews, observations, and secondary data in the form of court determination. The technical analysis of data used is qualitative approach to primary data and secondary data. The purpose of this research is what the judge considered in the Purworejo Religious Court in granting the application for marital dispensation on the determination No. 266/Pdt.P/2020/PA/Pwr, and to find out the determination of judges in the Purworejo Religious Court regarding marital dispensation which is analyzed through maslahah. Based on the results of the research conducted, it can be concluded that the consideration of the judge in granting the request for marital dispensation is on the grounds that the marriage is urgent to be done, between the husband and wife there is no obstacle to marriage and the two families have approved each other. In the analysis maslahah consideration of judges included in the maslahah doruriyah because to maintain religion and descendants.